Value of cytoprognostic classification in breast carcinomas. Issue 5 (May 1986) - Mouriquand, J; Gozlan-Fior, M; Villemain, D; Bouchet, Y; Sage, J C; Mermet, M A; Bolla, M
Abstract : Two hundred and four cases of breast carcinoma were classified according to cytological features, and these were related to prognosis. A disease free interval of seven years was 95% for patients with grade I, 70% for those with grade II, and 45% for those with grade III tumours. The risk of recurrence was also related to tumour size and the presence or absence of steroid receptors in the tumour. Cytological classification of breast carcinoma based on fine needle aspiration provides valuable information concerning the prognosis of patients, which is relevant to their clinical management.